(untitled) (International Journal of Engineering and Computer Science, 2015)
This research work has proposed a improved gradient based sorted switching median filter for highly corrupted medical images. It has the capability to decrease the high thickness of noise from medical photos and also conduct better around the others when input picture is noise-less. The proposed technique has additionally capability to conserve the edges by usage of the gradient based smoothing. The proposed approach has been developed and executed in MATLAB 2013a tool using image processing toolbox. Various kinds of the medical photos have been taken for experimental purpose. Comparative examination has shown that the proposed algorithm is efficient compared to available techniques.